A Critical Study of the Relationship of Faith and Action - Ahmad Hossein Fallahi, Majid Tavakkol, Yadollah Dadjoo, Seyyed Hassan Bathayi, (Opción, 2019)
The aim of the study is to investigate a critical study of the relationship of faith and action from the Muslim thinkers’ point of view. The methodology of current research is library based studies on the ideas of Muslim thinkers including theologians and philosophers. As a result, the action plays a decisive role in the levels of faith; because mere faith and without action is not a perfect faith. In conclusion, the chosen view is that the minimum faith is attestation or confession but with reaching the higher levels of faith one must pass through the stages of righteous action.